2018
DOI: 10.1017/jwe.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Banks in the Lifecycle of Bordeaux Wine Cooperatives

Abstract: In this article, we investigate a possible conflict between two core objectives of cooperatives, members’ income, and continuity, by examining the link between debt and the price paid to producers for Bordeaux wine cooperatives, according to their downstream strategies: (1) the traditional strategy, which is to sell wine in bulk to négociants; (2) joining a federation of cooperatives which blends and puts the wine in the retail market; and (3) vertical integration. We show that downstream strategies are relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, none of the positive configurative strategies of Miles and Snow are related to their better performance, though the study reported that, by avoiding a reactor strategy, a firm can attain a better performance. The conclusions reached about the differences in business performance between cooperatives and IOFs are in line with the study by Sexton and Iskow (1993), who defended the idea that cooperatives do not have a lower performance, even though members' return and continuity are the core objectives of cooperatives (Cadot and Ugaglia, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…However, none of the positive configurative strategies of Miles and Snow are related to their better performance, though the study reported that, by avoiding a reactor strategy, a firm can attain a better performance. The conclusions reached about the differences in business performance between cooperatives and IOFs are in line with the study by Sexton and Iskow (1993), who defended the idea that cooperatives do not have a lower performance, even though members' return and continuity are the core objectives of cooperatives (Cadot and Ugaglia, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Declerck and Viviani [11] identify a capacity of cooperatives to absorb fluctuations at the expense of their members. Cadot and Ugaglia [12] examine the organizational strategies of Bordeaux wine cooperatives in relation to member incomes highlighting the importance of downstream strategies for cooperatives to pursue. They examine the link between leverage (being a proxy for debt) and prices paid to grape producers and show that the downstream organizational strategies chosen (including exit and vertical integration) are critically related to the lending regime.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Moreover, extant research customarily has neglected to specifically address the nature of cooperative distinctiveness interlinked with the pursuit of dual performance objectives [21,27,28], having favored the corporate over the member orientation. Prior work has focused on readily available financial accounting measures commonly used to evaluate investor-owned firms (IOFs) or has applied advanced quantitative techniques (e.g., data envelopment analysis) to estimate economic and technical efficiency [22].…”
Section: Introductionmentioning
confidence: 99%